Benzene Exposure on Rig X from Drilling Fluid and Effectiveness of Local Exhaust Ventilation - William William; Sjahrul Meizar Nasri (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: Benzene is a carcinogenic compound commonly found in drilling fluid, a chemical used in oil and gas drilling operations. Benzene exposure to workers is known to cause acute and/or chronic disease. Adequate control measures shall be identified and implemented to prevent the adverse health effects of benzene from the utilization of drilling fluid. Methods: This study measured benzene concentrations at several locations, above the drilling rig, which has the potential risk of benzene vapor exposure. From the measurement results, if the threshold limit value was exceeded, LEV was proposed to be installed and the effectiveness of LEV at each location would be assessed. A two-tailed t-test was used with a confidence level of 95% (α=0.05) to measure the effectiveness of LEV. Results: In several areas, benzene concentration exceeded TLV-TWA, and LEV was installed in those areas as control measures. In this study, it was found that LEV was not always effective in reducing the concentration of benzene in some areas. Conclusion: Drilling fluid was essential for drilling activity, and this could cause benzene vapor to contaminate the working area. The installation of the LEV shall consider the type of containment through which the drilling fluid flows to ensure the mitigation measures are effective to reduce the concentration of benzene in the air that may be exposed to workers.Keywords: benzene, drilling fluid, exhaust ventilation